Realizing the right to education in Egypt: an assessment of primary education in relation to international standards - Qadir, Fawziah Abdel Rahman (AUC Knowledge Fountain, 2012)
The right to education in international human rights law is contained in number of international treaties. The most comprehensive coverage of the right is found within the International Covenant on Economic, Social and Cultural Rights (ICESCR) under articles 13 and 14. The primary level of education is an essential and integral phase in the development of a child, without the right to education children are unable to realize other rights. This research assesses the functionality of the Egyptian primary education system and its compliance with the international human rights standards of education, specifically the utilizing the 4-A schematic. The indicators included in the 4-A system are defined and analyzed in accordance to the primary level of education. A brief modern history of the Egyptian education system is provided in order to understand current trends. The issues facing the Ministry of Education â are centralization, aid for education and social and economic gaps â and their analysis provides greater insight into the compliance of the state. The final section of this research measures and analyzes the Egyptian system with the international standards in direct correlation to the human rights indicators that comprise the 4-A schematic. There are pockets of defacto discrimination, mostly social-economic that exists within the Egyptian primary education system and by international standards these facets of discrimination should take the highest priority for reform for the Ministry of Education. Other elements detracting from the provision of the right to education includes the quality of education in Egypt and equality. Stronger educational policies that are sharply focused, with targets for implementation being set; comprehensive legislation; and greater levels of awareness and civic engagement are needed in order to protect the right to education at the primary education level.